ØªØ·ÙˆÙŠØ± ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…Ù†ØªÙ‚Ù„ (M-Learning) Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ AndroidÙ„ØªØ¹Ù„ÙŠÙ… Ø¨Ø§Ø¨ "Ø§Ù„Ù…Ù‡Ù†Ø© ÙˆØ§Ù„ØÙŠØ§Ø©" ÙÙŠ Ù…Ø§Ø¯Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© (Ø¨Ø§Ù„ØªØ·Ø¨ÙŠÙ‚ Ø¹Ù„Ù‰ Ø§Ù„ØµÙ Ø§Ù„Ø¹Ø§Ø´Ø± ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© "Ù…Ø¯Ø§Ù† Ø§Ù„ØªØ¹Ù„ÙŠÙ…" Ù…Ø§ÙŠØ§Ù†Ø¬Ø§Ù† Ø¬ÙˆÙƒÙˆØ±ÙˆØ·Ø§ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬) - Iâ€™anatul Faqiroh; Fathur Rohman; Restu Budiansyah Rizki (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2021)
Arabic language learning at Madrasah Aliyah Midanutta'lim Mayangan Jogoroto Jombang only uses package books, and not all students can get the package book. While smartphones are only for communication tools for students. One of the learning media innovations that can be used effectively and efficiently in learning is android-based mobile learning (m-learning) media. This technology can be developed for Arabic language learning. This study aims to: (1) Develop mobile learning media-based material al-mihnatu wa al-hayatu students of grade ten even semesters in Madrasah Aliyah Midanutta'lim Mayangan Jogoroto Jombang, (2) Knowing the effectiveness and effectiveness of the learning media developed. This research is a research development or Research and Development (R&D) using addie development model. This model has five stages, namely: Analysis Stage, Design Stage, Development Stage, Implementation Stage, and Evaluation Stage. The validators in this study are material experts and media experts. The subjects of the study were lecturers, teachers, and tenth graders majoring in social sciences at MA Midanutta'lim Mayangan Jogoroto Jombang. Data collection using questionnaires, interview guidelines and observation sheets. The data collection method in this study uses a simple percentage formula. The results of this study are: (1) The process of developing learning media based on mobile learning material al-mihnatu wa al-hayatu, (2) The quality of media developed is very feasible with a percentage of 96% by material experts, and very feasible with a percentage of 94% by media experts. This development product has been proven interesting and effective to increase students' learning interest based on the results of questionnaires obtained from respondents, namely tenth graders majoring in IPS at MA Midanutta'lim Mayangan Jogoroto Jombang with a percentage of 95%. It can be concluded that the arabic language learning media based on mobile learning developed is very feasible and very effective for Arabic language learning.